2020
DOI: 10.3390/ijms21030780
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence and QTL Analyses Using Backcross Recombinant Inbred Lines (BILs) and BILF1 Lines Uncover Multiple Heterosis-related Loci

Abstract: Heterosis is an interesting topic for both breeders and biologists due to its practical importance and scientific significance. Cultivated rice (Oryza sativa L.) consists of two subspecies, indica and japonica, and hybrid rice is the predominant form of indica rice in China. However, the molecular mechanism underlying heterosis in japonica remains unclear. The present study determined the genome sequence and conducted quantitative trait locus (QTL) analysis using backcross recombinant inbred lines (BILs) and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Correlation coefficients are used to measure relationship between two variables as evident from positive correlation of yield components with GY except for FAR and highly significant for PE, PM, FP and AH traits, however, the negative correlation and significant was found with AH (Table 3). (Yu et al, 2020 found the correlation between the introgression rate of the Habataki pedigree and yield related traits, whereas the introgression rate was significantly negatively correlated to 1000-grain mass. Li et al (2019) found that correlations between agronomic traits and yield depend on the rice variety.…”
Section: Specific Combining Ability (Sca) Ef-fectsmentioning
confidence: 88%
See 1 more Smart Citation
“…Correlation coefficients are used to measure relationship between two variables as evident from positive correlation of yield components with GY except for FAR and highly significant for PE, PM, FP and AH traits, however, the negative correlation and significant was found with AH (Table 3). (Yu et al, 2020 found the correlation between the introgression rate of the Habataki pedigree and yield related traits, whereas the introgression rate was significantly negatively correlated to 1000-grain mass. Li et al (2019) found that correlations between agronomic traits and yield depend on the rice variety.…”
Section: Specific Combining Ability (Sca) Ef-fectsmentioning
confidence: 88%
“…The three-line system is based on a cytoplasmic male sterile (CMS) line, a restorer line (to produce F 1 hybrid seeds) and a CMS maintainer line (to maintain the CMS line). The two-line hybrid system is based on environmentally sensitive genetic male sterility (Yu et al, 2020)" and it usually uses photoperiod-and thermo-sensitive genic male sterile (PTGMS) lines as maternal parents to produce hybrid seeds. PTGMS lines are sterile under restrictive conditions (high temperatures and long days) but become fertile under permissive conditions such as low temperatures and short days (Lan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Heterosis is a phenomenon in which F 1 hybrid progenies exhibit superior performances compared with those of their parents [1][2][3]. It is used for hybrid crop breeding, which has greatly increased the productivity of many crops worldwide [4,5]. The successful exploitation of heterosis has also led researchers to determine its essential features.…”
Section: Introductionmentioning
confidence: 99%
“…Heterosis is a phenomenon in which F1 hybrid progeny exhibit superior performances compared with those of their parents [1][2][3]. It is used for hybrid crop breeding, which has greatly increased the productivity of many crops worldwide [4,5]. The successful exploitation of heterosis has also led researchers to determine its essential features.…”
Section: Introductionmentioning
confidence: 99%